(3JWHjbGJ HGSJNOGe HQeLjI (Bstatas - (3CThGb(B, (3Hf bOhQs ((3GdLRGFQ(B:s (3OGQ GdcJGH GdYQHj(B,s, 2021)
(3eaGgje CSGSjI, echfGJ GdSdGSd GdRefjI, CSGdjH GdeJhSWGJ GdeJMQcI, bjGS GdGJLGg GdYGe, GdJfHD HhLhO GdJCKjQGJ GdehSejI, GdJegjO GdCSj, JMdjd GdGQJHGW hGdGfMOGQ, GSJNOGeGJ hJWHjbGJ HQfGeL (Bstata (3aj JMdjd GdSdGSd GdRefjI(B.s
(3eQGLY U(B.197s
Keywords: (3GdGMUGAs; (3GdSdGSd GdRefjIs